QTL mapping of genome regions controlling temephos resistance in larvae of the mosquito Aedes aegypti. - Guadalupe Del Carmen Reyes-Solis; Karla Saavedra-Rodriguez; Adriana Flores Suarez; William C Black (Public Library of Science (PLoS), 2014)
The mosquito Aedes aegypti is the principal vector of dengue and yellow fever flaviviruses. Temephos is an organophosphate insecticide used globally to suppress Ae. aegypti larval populations but resistance has evolved in many locations.Quantitative Trait Loci (QTL) controlling temephos survival in Ae. aegypti larvae were mapped in a pair of F3 advanced intercross lines arising from temephos resistant parents from Solidaridad, México and temephos susceptible parents from Iquitos, Peru. Two sets of 200 F3 larvae were exposed to a discriminating dose of temephos and then dead larvae were collected and preserved for DNA isolation every two hours up to 16 hours. Larvae surviving longer than 16 hours were considered resistant. For QTL mapping, single nucleotide polymorphisms (SNPs) were identified at 23 single copy genes and 26 microsatellite loci of known physical positions in the Ae. aegypti genome. In both reciprocal crosses, Multiple Interval Mapping identified eleven QTL associated with time until death. In the Solidaridad×Iquitos (SLD×Iq) cross twelve were associated with survival but in the reciprocal IqxSLD cross, only six QTL were survival associated. Polymorphisms at acetylcholine esterase (AchE) loci 1 and 2 were not associated with either resistance phenotype suggesting that target site insensitivity is not an organophosphate resistance mechanism in this region of México.Temephos resistance is under the control of many metabolic genes of small effect and dispersed throughout the Ae. aegypti genome.